Determinants of severe acute malnutrition among under 5 children in Satar community of Jhapa, Nepal. - Kajol Dahal; Deepak Kumar Yadav; Dharanidhar Baral; Birendra Kumar Yadav (PLoS ONE)
Background Severe acute malnutrition (SAM) is the most extreme and visible form of undernutrition plagued by chronic poverty, household food insecurity, lack of education. One of the indigenous and marginalized community of Nepal, Satar/Santhal has often been neglected and is devoid of good education and are economically deprived. This predisposes under 5 children of Satar into malnutrition. The study aims to assess determinants of SAM among children under 5 years of age in Satar community of Jhapa district, Nepal. Material & methods A community based matched case control study was carried from September 2019 to February 2020 among under five children of Satar community residing in Jhapa district. Multistage random sampling technique was used to select 50 cases and 100 controls in the ratio of 1:2. Information was collected through personal interview with the parents and anthropometric measurement of the children was measured. Bivariate and multivariate conditional logistic regression analysis was used to explore the determinants of severe acute malnutrition. Results A total of 664 children between the age group of 6-59 months were screened for SAM. The prevalence of SAM was found 7.53%. Factors like, low economic status, birth interval less than 2 years, frequency of breast feeding <8 times/day and household food insecurity were found to be significant determinants of SAM. Multivariate logistic regression documented low economic status (AOR: 11.14, 95% CI 1.42 to 87.46); and frequency of breast feeding <8 times/day (AOR: 2.09, 95% CI 1.00 to 4.37) as determinants of SAM. Conclusion Low economic status and frequency of breast feeding less than 8times/day were major determinants of SAM among children under 5yrs of age. Ending malnutrition will require greater efforts and integrated approaches to eradicate extreme poverty. Multi-sector approaches have been conducting for SAM in Nepal but there are no specific approaches for marginalized community.